The Effect of Economic Growth, Interest Rates, Remittances, and Green Investment on Foreign Direct Investment in Indonesia - Suprihatin, Luluk; Andrian, Thomas (International Journal of Social Science, Education, Communication and Economics, 2024)
This study aims to analyse the effect of economic growth, interest rates, remittances, and green investment on Foreign Direct Investment in Indonesia. This study uses time series data during the first quarter of 2013 to the fourth quarter of 2021 in Indonesia. The dependent variable used is Foreign Direct Investment and the independent variables include economic growth, interest rates, remittances, and green investment. The analytical tool used is multiple linear regression with the Error Correction Model (ECM) method. The results showed that economic growth in the short term and long term has a significant positive effect on foreign direct investment in Indonesia. Interest rates in the short term have a significant negative effect on foreign direct investment in Indonesia, while in the long term have no effect on foreign direct investment in Indonesia. Remittances in the short and long term have no effect on foreign direct investment in Indonesia. Green investment in the short term has no effect on foreign direct investment in Indonesia, while in the long term it has a significant negative effect on foreign direct investment in Indonesia.